1993
DOI: 10.1007/bf01308594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEG-electrolyte (colyte) lavage on serum acetaminophen concentrations

Abstract: The purpose of this study was to evaluate whole gut lavage with polyethylene glycol electrolyte solution (Colyte), as a potentially adjunctive measure in lowering serum acetaminophen levels. The effect of bowel lavage was evaluated on serial serum acetaminophen concentrations after 2-g and 4-g doses in 7 and 12 male patients, respectively. Mean peak level of serum acetaminophen after 2 g (60 min after intake) was not significantly lowered by bowel lavage. After 4 g, peak acetaminophen serum levels were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…One was a simulated overdose trial in volunteers (level 2b) that found no difference in AUC between controls and those receiving 25 g of activated charcoal 15 minutes after ingestion (110). A retrospective cohort (level 2b) study in children with actual overdoses found no difference in 4-hour serum acetaminophen concentrations between the activated charcoal and no decontamination cohorts (54).…”
Section: Gastrointestinal Decontaminationmentioning
confidence: 99%
“…One was a simulated overdose trial in volunteers (level 2b) that found no difference in AUC between controls and those receiving 25 g of activated charcoal 15 minutes after ingestion (110). A retrospective cohort (level 2b) study in children with actual overdoses found no difference in 4-hour serum acetaminophen concentrations between the activated charcoal and no decontamination cohorts (54).…”
Section: Gastrointestinal Decontaminationmentioning
confidence: 99%